PENGARUH KONSENTRASI AKTIVATOR KOH PADA KUALITAS KARBON AKTIF DARI KULIT SINGKONG - Mahirullah; Afrianti S. Lamuru; Rosalin; Suriadi; Nurfiansyah; Nangsih Sulastri Slamet; Hasni (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2026)
The aim of the research was to examine the effect of varying KOH concentrations on the properties of activated carbon produced from cassava peel waste. Cassava peel can produce activated carbon or charcoal as a result of the activation process using a physicochemical method utilizing chemical activators and chemical activation to obtain a high level of biomaterial composition and carbon content. Cassava peel charcoal will be soaked with a chemical activator (KOH) for 24 hours using different KOH concentrations, namely 1%, 2.5%, 5% and 10%. The properties of the activated carbon produced are determined by SNI No. 06-3730-1995. Tests will be carried out on iodine absorption capacity, water content and ash content as part of this characterization test. The results of this study indicate that the activated carbon produced from all treatments of KOH concentrations of 1%, 2.5%, 5% and 10% do not meet the SNI No. 16-3730-1995 standards for fixed carbon content (> 25%), volatile matter (< 65%) or iodine absorption capacity (< 750 mg / g). Activated carbon produced using 5% KOH had the best absorption capacity of 354.43 mg/g compared to the other three concentrations.